Discrimination Against Nonworkers in Nepal: Perceived Socio-Political, Economic, and Psychological Impacts - Aryal , Ananta (Journal of Productive Discourse, 2025)
This qualitative study examines the socio-political, economic, and psychological impacts of discrimination faced by nonworkers in Nepal. Based on 26 in-depth interviews and using thematic and narrative analysis, the research finds that unemployment in Nepal is not merely an economic issue but a deeply social experience shaped by stigma, inequality, and exclusion. Nonworkers face layered discrimination from families, communities, and institutions. Within families, they experience unequal emotional and financial support, rooted in cultural beliefs that link personal worth to employment. In their communities, they are often viewed as burdens, leading to isolation and low self-esteem. At the institutional level, state policies largely ignore the needs of the unemployed, denying them access to essential services such as healthcare, social security, and vocational training. Economic challenges are worsened by nepotism and favoritism in recruitment, limiting fair employment opportunities. Many nonworkers survive by borrowing money, relying on family support, or selling personal belongings. Socio-politically, nonworkers are excluded from public discourse and policy development, and increasing divisions between employed and unemployed individuals threaten social unity. Psychologically, participants reported high levels of distress, including anxiety, depression, and suicidal thoughts. Gender-based exploitation during job-seeking, particularly affecting women, emerged as a serious concern. The study calls for urgent policy reforms to ensure fair access to education and employment and to shift societal attitudes about unemployment. Addressing the structural, socio-political, economic, and psychological burdens of nonworkers is crucial to promoting dignity, mental health, and social integration in Nepali society.